Prevalence and patterns of dyslipidaemia and glycaemic abnormalities among patients of heart failure at a tertiary care hospital in Eastern India - Biswas, Soham; Sarkar, Pinaki; Patra, Tushar Kanti (International Journal of Research in Medical Sciences, 2026)
Background: Dyslipidaemia and diabetes mellitus are highly prevalent in India. Both are risk factors of various cardiovascular diseases which may progress to heart failure. Heart failure is a leading cause of morbidity and mortality throughout the world. This study aimed to estimate the prevalence of different patterns of dyslipidaemia and glycaemic abnormalities among the heart failure patients of different severity. Methods: A descriptive, cross-sectional study was done on 492 clinically diagnosed heart failure patients categorised according to severity based on NYHA classification. Serum lipid profile, fasting plasma glucose and HbA1c % were evaluated. Data were analysed using standard statistical software. Results: The different patterns of dyslipidaemia detected were hypercholesterolaemia (32%), increased LDL cholesterol (34%), decreased HDL cholesterol (52%) and hypertriglyceridaemia (26%). Prevalences of pre-diabetes and diabetes mellitus were 33 % and 29 % respectively. No patient had NYHA class I symptoms. Prevalence of hypercholesterolaemia among NYHA class II, III and IV patients were 28 %, 33 % and 40 % respectively whereas prevalence of hypertriglyceridaemia were 21%, 28% and 30% in the respective classes. Diabetes mellitus was present in 7%, 39%, and 50% of NYHA class II, III, and IV patients, respectively. Conclusions: The commonest form of dyslipidaemia was low HDL cholesterol, detected in almost half of the patients, followed by elevated LDL cholesterol. Hyperglycaemia was detected in almost two-thirds of the patients. Pre-diabetes was slightly more prevalent than diabetes mellitus. Prevalence of dyslipidaemia and diabetes mellitus increased with the severity of heart failure.